ENHANCING SUSTAINABILITY EFFORTS TO ADAPT TO CLIMATE CHANGE THROUGH MANGROVE PLANTING ON AMBALAT BEACH - Nur Fithriyanti Imamah; Jubaidi Jubaidi; Faried Rahman Hidayat; Romadhona Rusdi Ambar Sari (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
The purpose of this community service activity is to revitalize the degraded coastal ecosystem of Ambalat Beach through mangrove planting while also enhancing community awareness and capacity for sustainable coastal conservation. The methods applied include site surveys to determine suitable planting areas, participat ory education to improve community understanding of mangrove importance, and direct planting activities (action learning). A total of 1,000 mangrove seedlings of the species Rhizophora mucronata were successfully planted on selected potential land agreed upon by the local community. A participatory approach integrating local knowledge with scientific principles became a key factor in the implementation of this activity. The results indicate an increase in community understanding of the ecological functions of mangroves and proper planting techniques. Evaluation shows that some seed lings did not grow optimally due to environmental factors such as wave exposure, substrate conditions, the need for improved planting.